(3CUhd GdJShjb (B: (3eONd JMdjdj (B:s (3eONd JMdjdj (B((3eMce YdejG (B) /s - (3eYdG, fGLjs; (3QGFa, Jhajbs ((3YeGf(B: s (3OGQ hGFd ddfTQ(B, s, 2005)
(3ebOeI YGeI aj GdJShjb(B- (3GdHjFI GdJShjbjI(B- (3GdSdhc GdTQGFj(B- (3HMhK GdJShjb hCfXeI GdeYdheGJ(B- (3JLRFI GdShb hGdCShGb GdeSJgOaI(B- (3GdefJLGJ, CfhGYgG hNUGFUgG(B- (3GdJSYjQ hSjGSGJg(B- (3bfhGJ GdJhRjY(B- (3eDSSGJ GdJhRjY(B- (3GdJQhjL hCSGdjHg(B- (3JWhjQ hEHJcGQ GdefJLGJ GdLOjOIs
(3cTGa eUWdMGJ U(B.371s
Keywords: (3GdEbJUGO GdbjGSjs; (3GdJShjbs